Clinicopathological features and EBV infection status of lymphoma in children and adolescents in South China: a retrospective study of 662 cases - Changfei Qin; Yuhua Huang; Yanfen Feng; Min Li; Na Guo; Huilan Rao (BMC, 2018)
Abstract Background The clinicopathological features and Epstein-Barr virus (EBV) infection status of lymphoma in children and adolescents in South China is under-researched. South China is a well-known high-incidence area of EBV-associated nasopharyngeal carcinoma. Methods A cohort of 662 consecutive children and adolescents' lymphomas was retrospectively analyzed and Epstein-Barr virus encoded RNAs (EBERs) in situ hybridization was performed to detect the EBV infection. Results The majority (501/662, 75.7%) of lymphomas in children and adolescents was Non-Hodgkin lymphoma (NHL). One hundred sixty one cases (24.3%) were Hodgkin lymphoma (HL). Of the NHL, precursor cell lymphoma, mature B-cell lymphoma and peripheral T/NK-cell lymphoma accounted for 32.0%, 41.1% and 26.9% respectively. The five common subtypes were lymphoblastic lymphoma (32.0%), Burkitt lymphoma (BL) (21.0%), anaplastic large-cell lymphoma (ALCL) (14.2%), diffuse large B-cell lymphoma (DLBCL) (13.8%) and extranodal NK/T-cell lymphoma, nasal type (ENKTCL) (6.2%). EBV infection was detected in 58.9% classical Hodgkin lymphomas (CHLs), 21.4% mature B-cell lymphomas and 52.4% peripheral T/NK-cell lymphomas. Moreover, EBV was associated with high grade NHL including ENKTCL (100.0%), BL (30.5%) and DLBCL (17.6%). Conclusion The high proportion of peripheral T/NK-cell lymphomas in children and adolescents in South China are presented in this study and compared to western countries due to the high percentage of ENKTCL. ENKTCL is firmly associated with EBV infection, while more than half of HL, a portion of BL and DLBCL are related to EBV infection. This study conclusively demonstrates that EBV infection is more prevalent in children and adolescents with lymphomas in South China compared to western countries.